Edukasi Bahaya Musculoskeletal Disorders Pada Individu Dengan Aktivitas Duduk Lama - Juliastuti; yudiansyah (Khidmah, 2023)
Musculosceletal disorders (MSDs) are disorders that occur in musculoskeletals such as muscles, nerves, tendons, ligaments, joints, cartilage related to work and can cause complaints ranging from very mild complaints to very painful. One of the factors that can lead to the occurrence of MSDs is activity in a sitting position for a long time which lasts about two-thirds of working hours, and periods of sitting activity usually last at least 30 minutes. The disturbances felt vary based on the area of MSD complaints, in the upper extremity areas there can be complaints of neck muscle tension, rotator cuff tendinitis, shoulder impingement syndrome, lateral epicondylitis, carpal tunnel syndrome, wrist tendinitis and hand-arm vibration (HAV) syndrome. The method applied is to provide education about the dangers of MSDs and how to prevent MSDs. The results of the activity obtained educational videos on how to prevent MSDs which can be practiced in the general public and it is proven that these preventions can reduce pain in MSDs disorders. Keywords: Musculoskeletal Disorders (MSDs), Prolonged Sitting Activity.